2014
DOI: 10.1159/000363130
|View full text |Cite
|
Sign up to set email alerts
|

Acute Retinal Necrosis in Childhood

Abstract: Background: Acute retinal necrosis (ARN) is a viral syndrome consisting of uveitis/vitritis, occlusive vasculitis and peripheral necrosis. Few incidents are reported in children. The etiology is reactivated herpes simplex virus (HSV) or varicella-zoster virus (VZV). Treatment with acyclovir is often used. The administration of oral glucocorticosteroids is of unproven benefit. Prognosis is variable but poor. Methods: Three weeks after contracting mild chickenpox, a healthy 4-year-old girl developed blurred visi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 13 publications
0
3
0
Order By: Relevance
“…ARN syndrome generally has a poor prognosis ( 9 ) and can quickly affect the other eye if left untreated ( 30 ). Early diagnosis and therapy are key to maintaining vision and preventing the involvement of the other eye ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ARN syndrome generally has a poor prognosis ( 9 ) and can quickly affect the other eye if left untreated ( 30 ). Early diagnosis and therapy are key to maintaining vision and preventing the involvement of the other eye ( 16 ).…”
Section: Discussionmentioning
confidence: 99%
“…ARN syndrome is a serious viral infectious disease, and its main pathogenic viruses are varicella zoster virus (VZV), herpes simplex virus types 1 or 2, CMV, and the Epstein-Barr virus (EBV) (6)(7)(8). ARN can occur in both adults and children; however, it occurs more commonly in adults, with an average age of onset reported to be between 20 and 60 years (9). Several studies have reported that adult ARN is mainly due to VZV and HSV-1 (10).…”
Section: Discussionmentioning
confidence: 99%
“…The use of loaners and training with lower magnification may contribute to greater success for the patient and the provider. Providing handouts, follow‐up visits with demonstrations and peer group advice can be helpful for the new low vision patient …”
Section: Discussionmentioning
confidence: 99%